Kualitas Pelayanan Terhadap Kepuasan Konsumen PT Pos Indonesia Cabang Kota Baru Kalimantan Barat - Iis Dahlia; Resista Vikaliana; I Nyoman Purnaya (Forum Kerjasama Pendidikan Tinggi, 2022)
This study aims to determine the effect of service quality and customer satisfaction at PT Pos Indonesia Kota Baru branch, West Kalimantan. This study used 100 respondents as the research sample by distributing questionnaires. Sampling is accidental sampling. This study uses a quantitative approach to the type of correlational research. The data analysis technique used is simple linear regression analysis. The results showed a simple linear regression equation Y= 5.785 + 0.514X. This equation shows that the service quality variable has a positive effect on customer satisfaction at PT Pos Indonesia Kota Baru Branch, West Kalimantan. The results of hypothesis testing using the t-test indicate that the service quality variable has an effect on customer satisfaction at PT Pos Indonesia Kota Baru Branch, West Kalimantan. The magnitude of the influence of service quality on consumer satisfaction is indicated by the correlation coefficient value of 0.923, which means it is very strong. While the coefficient of determination is 0.852, which implies that the effect of the independent variable (X) on the dependent variable (Y) is 85.2%. The remaining 14.8% is influenced by other variables that are not studied or are not included in the model